Lignocellulose-based hard carbon active material, preparation thereof and application of lignocellulose-based hard carbon active material in sodium ion battery

By adopting a three -level liquid phase modification and gas -phase modification process in the biomass of wood cellulose to adjust its materialized structure, the performance of biomass hard carbon materials in sodium ion batteries is not ideal. High -efficiency and stable sodium ion battery electrochemical performance.

CN119330337AActive Publication Date: 2025-01-21CENT SOUTH UNIV

Patent Information

Application Number
CN202411493530.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-21
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The properties of lignocellulosic biomass precursors are complex and unstable, resulting in the reversible sodium storage capacity and rate performance of biomass-based hard carbon materials in sodium ion batteries, and it is difficult to take into account ultra-high rate and excellent first-effect performance.

Method used

Three -level liquid -phase modification of average, alkali, and acid, combined with the gas modification of oxygen -containing atmosphere, and the two -stage thermal treatment of the auxiliary agent, adjust and the materialized structure of biochemical biomass, thereby optimizing the sodium storage of hard carbon. Ability and sodium ion transmission pathway and efficiency.

Benefits of technology

The prepared lignocellulose-based hard carbon active material has ultra-high rate, excellent first efficiency and stability, and significantly improves the electrochemical performance of sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330337A_ABST
    Figure CN119330337A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of negative electrode materials, and particularly discloses a lignocellulose-based hard carbon active material preparation method, which comprises: placing lignocellulose biomass in a solution A containing a homogenizing agent, carrying out liquid phase modification at a temperature T1, carrying out solid-liquid separation, and collecting to obtain a modified biomass A; sequentially carrying out alkali liquor modification and acid liquor modification treatment on the modified biomass A to obtain modified biomass B; the homogenizing agent is a compound capable of ionizing NH4 < + > ions; carrying out gas phase modification treatment on the modified biomass B in an oxygen-containing atmosphere at the temperature T2 to obtain modified biomass C; and mixing the modified biomass C with an auxiliary agent, carrying out first-stage heat preservation at the temperature T3 in advance, and then carrying out second-stage heat preservation at the temperature T4 to prepare the lignocellulose-based hard carbon active material. The invention also comprises the material prepared by the method and application of the material in a sodium ion battery. The method provided by the invention can be used for preparing the hard carbon material with ultrahigh multiplying power and excellent first effect and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion battery negative electrode materials, and in particular relates to the field of sodium ion battery hard carbon negative electrode materials based on lignocellulosic biomass. Background Art

[0002] In recent years, the development and utilization of renewable energy and the application of zero-emission electric vehicles have attracted much attention as an effective way to limit carbon emissions. In order to achieve energy transformation and sustainable development, it is urgent to develop efficient and low-cost mobile and fixed energy storage systems. As one of the most advanced energy storage technologies, lithium-ion batteries are widely used in electronic equipment, transportation, radio communications and other fields. However, the rich application scenarios and limited and unevenly distributed lithium resources will limit the application of lithium-ion batteries in zero-emission electric vehicles and large-scale energy storage. Due to their lower cost and similar working principles, sodium-ion batteries are considered to be a beneficial supplement to lithium-ion batteries.

[0003] Due to thermodynamic factors and the problem of small interlayer spacing, sodium-ion batteries usually use hard carbon materials as negative electrodes instead of commercial graphite materials. Hard carbon refers to carbon materials that are difficult to graphitize. Its microstructure contains both graphite crystallites formed by short carbon layers and amorphous regions. This structural feature enables hard carbon materials to provide more sodium storage sites and have higher specific capacity.

[0004] Among the many precursors of hard carbon materials, biomass is considered to be one of the most promising precursors due to its wide sources and low cost. As the most abundant biological resource on earth, lignocellulosic substances are a type of biopolymer with cellulose, hemicellulose and lignin as the main components. They include agricultural waste, agricultural derivatives, plants, wood and many other types, and their sources are very wide. However, the complex chemical composition and unstable properties will have an adverse effect on the electrochemical properties of its derived hard carbon materials, posing challenges to large-scale production and application. In addition, under the joint influence of the precursor properties and the preparation process, the obtained hard carbon materials exhibit a turbulent layer disordered structure, and the complex structural characteristics play a decisive role in its sodium storage performance. Therefore, the development of low-cost and high-efficiency biomass precursor property regulation and heat treatment process will help solve the consistency and stability problems of biomass-based hard carbon negative electrode materials, while achieving further improvement in their sodium storage performance.

[0005] The prior art usually uses chemical pretreatment to regulate the properties of biomass, and controls the microstructure of hard carbon materials by controlling the temperature and time of the high-temperature carbonization stage. For example, in the Chinese patent document with publication number CN117613268A, a mixed solution of sodium hydroxide and sodium chlorite is used to modify lignocellulosic biomass to reduce the lignin content therein, and the sodium ion battery under the preferred scheme exhibits a reversible capacity of 259.3mAh / g and a first-week coulomb efficiency of 82.1%. The Chinese patent document with publication number CN118173787A carbonizes the esterified modified biomass three times to prepare a hard carbon negative electrode material, which exhibits a high sodium storage capacity, as well as good rate performance and cycle stability. The Chinese patent document with publication number CN115259136A mixes the lignin extracted from the biomass with a pore-forming agent, and then performs pre-carbonization and high-temperature carbonization in sequence to obtain a hard carbon material. The abundant micropores in its structure make the material have a high first discharge capacity, but the first coulomb efficiency needs to be improved.

[0006] In summary, the research on the properties of lignocellulosic biomass precursors, the regulation of hard carbon pore structure and thermal treatment process is still relatively scarce, and the universality of the process, the reversible sodium storage capacity and rate performance of hard carbon materials still need to be further improved. Summary of the invention

[0007] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a lignocellulose-based hard carbon active material, aiming to prepare a hard carbon active material with excellent performance such as excellent rate and first effect.

[0008] The second object of the present invention is to provide a lignocellulose-based hard carbon active material obtained by the preparation method and its application in sodium ion batteries.

[0009] The third object of the present invention is to provide a sodium ion battery comprising the lignocellulose-based hard carbon active material, and a negative electrode and a negative electrode material thereof.

[0010] The biomass raw materials are complex and unstable in nature, and the reversible sodium storage capacity and rate performance of biomass-based hard carbon materials when used as negative electrodes of sodium ion batteries are not ideal. In addition, the existing hard carbon materials are also difficult to take into account both ultra-high rate and first-efficiency performance. Through research, the present invention provides the following improvement scheme:

[0011] A method for preparing a lignocellulose-based hard carbon active material, comprising:

[0012] Step (1):

[0013] The lignocellulosic biomass is placed in a solution A containing a homogenizer and subjected to liquid phase modification at a temperature T1, followed by solid-liquid separation, and the modified biomass A is collected; the modified biomass A is then subjected to alkali modification and acid modification treatment in sequence to obtain a modified biomass B;

[0014] The homogenizer is capable of ionizing NH4 + Ionic compound; the temperature T1 is 40 to 120°C;

[0015] Step (2):

[0016] The modified biomass B is subjected to gas phase modification treatment in an oxygen-containing atmosphere at a temperature T2 to obtain a modified biomass C; the temperature T2 is 200 to 400° C.;

[0017] Step (3):

[0018] The modified biomass C and the additive are mixed, and the mixture is pre-heated at a temperature T3 for a first stage, and then heat-insulated at a temperature T4 for a second stage to obtain the lignocellulose-based hard carbon active material;

[0019] The auxiliary agent includes a transition metal source; the temperature T3 is 700-900°C; and the temperature T4 is 1000-1300°C.

[0020] The present invention innovatively adopts three-stage liquid phase modification of homogenizer, alkali and acid, and further cooperates with gas phase modification under oxygen-containing atmosphere and two-stage heat treatment assisted by additives. This can unexpectedly adjust and homogenize the physicochemical structure of biomass, thereby facilitating the optimization of the sodium storage capacity of the hard carbon obtained and the sodium ion conduction pathway and efficiency, thereby obtaining a hard carbon material with ultra-high rate and excellent first effect and stability.

[0021] The technical solution described in the present invention has good universality and can be adapted to any lignocellulosic biomass raw materials known in any industry. For example, the lignocellulosic biomass contains lignocellulose, preferably including at least one of agricultural waste, agricultural derivatives and wood.

[0022] In the present invention, the agricultural waste includes at least one of rice straw, wheat straw, corn straw, bean straw, peanut straw, rape straw, sugarcane straw, cotton stalk, rice straw, bagasse, coconut shell, walnut shell, hazelnut shell, almond shell, macadamia shell, banana peel, grapefruit peel and orange peel.

[0023] In the present invention, the agricultural derivatives include at least one of corn cobs, lotus pods, oak seeds, pine cones, bamboo stalks, and reeds.

[0024] In the present invention, the wood includes at least one of pine, camphor, poplar, oak and fir.

[0025] In the present invention, the combination of the three-stage liquid phase modification, gas phase modification and the two-stage heat treatment assisted by additives is the key to synergistically optimizing the physical and chemical structure of biomass cellulose, thereby giving the prepared hard carbon material excellent fast charging, initial effect and stability performance.

[0026] In the present invention, the biomass is innovatively pre-treated with liquid phase heat preservation in a homogenizer, which can soften and homogenize the composition characteristics of the biomass, facilitate combination with other processes, and enhance the performance of the prepared hard carbon material such as the rate and first effect.

[0027] In the present invention, the homogenizer includes one or more of ammonium oxalate, ammonium chloride, ammonium bifluoride, ammonium formate, ammonium citrate, ammonium fluoroborate, and ammonium fluoride; preferably at least one of ammonium fluoride, ammonium bifluoride, and ammonium fluoroborate. The present invention also shows that under the preferred homogenizer, it can further cooperate with the process, which helps to further enhance the performance of the prepared hard carbon material, such as the rate and the first effect.

[0028] In the present invention, the homogenizer is 0.05-5% by weight of the lignocellulosic biomass; further, it can be 1-5%.

[0029] In the present invention, the liquid phase modification treatment stage is pressurized by atmosphere A; the atmosphere A is at least one of nitrogen, argon, carbon dioxide, and air. The present invention also shows that the liquid phase modification system is subjected to gasification and pressurization treatment, which can further enhance the liquid phase modification effect of the homogenizer and the temperature, and can further enhance the rate and initial effect of the prepared hard carbon material.

[0030] Preferably, the pressurized pressure is 0.2 to 0.5 MPa.

[0031] In the present invention, the solvent in the liquid phase modification stage is an aqueous solvent; preferably water or a water-organic solvent mixed solvent; the organic solvent is a water-soluble organic solvent, and more preferably a C1-C6 alcohol. The present invention also shows that the combined control of the solvent system for liquid phase modification, especially in the combined system of water-organic solvent, can unexpectedly further strengthen the modified liquid phase of the homogenizer, and can further strengthen the rate and the first effect of the prepared hard carbon material. In the present invention, the content of the organic solvent in the water-organic solvent mixed solvent can be reasonably adjusted as needed, for example, it can be less than 20v%, and further can be 1-20v%.

[0032] Preferably, the temperature of the liquid phase modification is 80-90°C.

[0033] Preferably, the liquid phase modification time is 4 to 8 hours.

[0034] In the present invention, after liquid phase modification, drying and pulverization can be performed as required, and the median particle size of the modified biomass can be controlled to be 50 to 75 μm as required.

[0035] In the present invention, after the liquid phase modification, the biomass may be further treated with alkaline solution in advance and then with acid solution, which helps to optimize the physicochemical characteristics of the biomass and further enhance the rate and initial effect of the prepared hard carbon material.

[0036] In the present invention, the alkaline solute in the alkali solution includes at least one of hydroxide and carbonate of an alkali metal.

[0037] In the present invention, the concentration of the alkaline solute in the alkali solution is 0.5 to 3M.

[0038] In the present invention, the temperature of the alkali solution treatment stage is not particularly limited, and can be, for example, 20°C or higher, and further can be 40 to 80°C.

[0039] In the present invention, the time of alkali solution modification is 4 to 12 hours.

[0040] In the present invention, the acidic solute in the acid solution includes at least one of hydrochloric acid, sulfuric acid, phosphoric acid and nitric acid.

[0041] In the present invention, the temperature of the acid solution treatment stage is not particularly limited, and can be, for example, 20°C or higher, and further can be 20 to 50°C.

[0042] In the present invention, the concentration of the acidic solute in the acid solution is 2-6M.

[0043] In the present invention, the time for acid modification is 4 to 12 hours.

[0044] In the present invention, the alkali solution modification and / or acid modification stage may be carried out under pressure, and the pressure of the pressurization may be, for example, 0.2 to 0.5 MPa.

[0045] In the present invention, based on the three-stage liquid phase treatment in step 1, further coordination with the subsequent gas phase treatment in an oxygen-containing atmosphere helps to further optimize the network structure of cellulose, thereby helping to optimize the hard carbon network, improve the electron and ion conduction pathways, and further help to improve the prepared hard carbon's performance such as the rate and first effect.

[0046] In the present invention, the oxygen-containing atmosphere is at least one of oxygen, air, oxygen-diluent mixed gas, and air-diluent mixed gas. The diluent is, for example, nitrogen, inert gas, carbon dioxide, etc.

[0047] In the present invention, the content of oxygen in the oxygen-containing atmosphere can be adjusted as needed, for example, it can be 5 to 35% by volume, and further can be 15 to 25%.

[0048] In the present invention, the modified biomass B is pre-mixed with an additive and then subjected to a gas phase modification treatment in the oxygen-containing atmosphere; wherein the additive comprises at least one of ammonium persulfate, sodium persulfate, potassium ferrate and sodium ferrate.

[0049] The research of the present invention also shows that on the basis of the gas phase modification, further adding certain additives can further optimize the network structure of cellulose, which helps to improve the rate and initial effect of the prepared hard carbon.

[0050] In the present invention, the additive accounts for 5 to 25% by weight of the modified biomass B, and can further account for 10 to 20% by weight.

[0051] Preferably, the gas-solid modification process is carried out in a rotary kiln or a fluidized bed furnace. Studies have also shown that under this preferred treatment process, the network structure of cellulose can be dynamically optimized, which helps to improve the performance of the prepared hard carbon, such as the rate and first effect.

[0052] Preferably, the temperature of the gas phase modification is 250-350°C.

[0053] Preferably, the time of gas phase modification is 1 to 5 hours.

[0054] In the present invention, the modified biomass C is subjected to the two-stage treatment with the aid of an auxiliary agent, which helps to optimize the physical and chemical structure of the hard carbon and unexpectedly endows the prepared hard carbon with excellent performances such as rate and first effect.

[0055] In the present invention, in step (3), the auxiliary agent includes at least one of sodium hexafluoroferrate, potassium hexafluoroferrate, ferric trifluoromethanesulfonate, potassium ferrocyanide, sodium ferrocyanide, nickel trifluoromethanesulfonate, nickel tetrafluoroborate, cobalt trifluoromethanesulfonate, and potassium cobalt cyanide.

[0056] Preferably, the auxiliary agent further comprises an auxiliary agent, and the auxiliary agent comprises at least one of sodium trifluoromethanesulfonate, sodium carbonate, sodium hydroxide, and sodium carboxylate. The present invention also shows that further adding a certain auxiliary agent to the auxiliary agent can further optimize the performance of the prepared hard carbon, such as the rate and the first effect.

[0057] Preferably, the content of the auxiliary agent in the auxiliary agent is less than 50 wt %, and can further be 5-15 wt %.

[0058] Preferably, the auxiliary agent accounts for 0.5-10% by weight of the modified biomass C, and more preferably 4-8%.

[0059] Preferably, the insulation time in the first insulation stage can be 1 to 2 hours.

[0060] Preferably, the second insulation period may last for 1 to 3 hours.

[0061] The present invention also provides a lignocellulose-based hard carbon active material prepared by the preparation method.

[0062] The preparation method of the present invention can give the prepared material special physical and chemical characteristics, and the material prepared by the preparation method has excellent electrochemical properties such as excellent rate and first effect.

[0063] The present invention also provides an application of the lignocellulose-based hard carbon active material, which is used as a negative electrode active material for preparing a sodium ion battery.

[0064] The present invention also provides a sodium ion battery, which comprises the lignocellulose-based hard carbon active material prepared by the preparation method of the present invention;

[0065] Preferably, the negative electrode of the sodium ion battery contains the lignocellulose-based hard carbon active material.

[0066] Beneficial Effects

[0067] (1) The present invention innovatively adopts a three-stage liquid phase modification of a homogenizer, an alkali, and an acid, and further cooperates with a gas phase modification in an oxygen-containing atmosphere and a two-stage heat treatment assisted by an additive. This can unexpectedly adjust and homogenize the physicochemical structure of the biomass, thereby facilitating the optimization of the sodium storage capacity of the hard carbon obtained and the sodium ion conduction pathway and efficiency, thereby obtaining a hard carbon material with an ultra-high rate and excellent first effect and stability.

[0068] (2) The present invention also shows that the combined control of the homogenizer in the liquid phase treatment stage, the gas pressure of the liquid phase modification, the solvent, etc. can further enhance the synergy of the process, further optimize the sodium storage capacity of the prepared hard carbon and the sodium ion conduction efficiency and pathway, and help to further improve the fast charging performance of the prepared material.

[0069] (3): The present invention also shows that the sodium storage capacity and fast charging performance of the prepared material can be further enhanced by adding certain additives during the gas-solid modification stage and / or by using a rotary kiln or a boiling furnace for dynamic gas-solid treatment.

[0070] (4): Joint control of the types of auxiliary agents and / or auxiliary addition of auxiliary agents can help further enhance the sodium storage capacity and fast charging performance of the prepared materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Attached Figure 1 TEM image of the final hard carbon material obtained in Example 1;

[0072] Attached Figure 2This is the XRD pattern of the final hard carbon material obtained in Example 1;

[0073] Attached Figure 3 This is the first charge and discharge curve of the final hard carbon negative electrode material obtained in Example 1 at a current density of 30 mA / g;

[0074] Attached Figure 4 This is the rate cycle diagram of the final hard carbon negative electrode material obtained in Example 1 at current densities of 0.1C (1C=500mA / g), 0.2C, 0.4C, 1C, 2C, 4C, 10C, and 20C. DETAILED DESCRIPTION

[0075] The specific steps of the present invention are described below by way of examples. It should be understood that these examples are only for illustrating the present invention and are not intended to limit the scope of the present invention in any way. Various processes and methods not described in detail in the present invention are conventional methods known in the art.

[0076] A preferred method for preparing a sodium ion battery hard carbon negative electrode active material based on lignocellulosic biomass of the present invention comprises the following steps:

[0077] Step (1): placing lignocellulosic biomass (hereinafter referred to as biomass) in an aqueous solution containing a homogenizer for liquid phase modification and then drying, wherein the amount of the homogenizer added is 2-4% of the mass of the biomass, the liquid phase modification temperature is 90-100° C., the liquid phase modification time is 2-8 hours, the drying temperature is 60-80° C., the drying time is 12-24 hours, and after drying, the biomass is crushed and sieved to obtain a powder;

[0078] Step (2): The biomass powder obtained in step (1) is subjected to two-stage pretreatment, and then washed and dried to obtain modified biomass powder.

[0079] The concentration of the alkali solution is 0.5-3M, the liquid-to-solid ratio (ml / g) is (2-10):1, the reaction time is 4-12h, and the obtained powder is washed with water and dried after the reaction is completed; then the powder that has completed the first stage of acid treatment is placed in at least one acid solution of hydrochloric acid, sulfuric acid, and nitric acid for ultrasonic-assisted acid treatment, the acid solution concentration is 2-6M, the liquid-to-solid ratio (ml / g) is (2-6):1, the reaction temperature is 30-60°C, the reaction time is 4-12h, and the obtained powder is conventionally washed with water and dried after the reaction is completed;

[0080] Step (3): placing the powder obtained in step (2) in an atmosphere furnace for gas phase modification, introducing a mixture of inert gas and oxygen (volume ratio 10% to 20%) or air, the pre-carbonization temperature T1 is 200 to 400° C., preferably 250 to 350° C., the time is 1 to 5 hours, preferably 2 to 4 hours, and the heating rate is 0.5 to 10° C. / min;

[0081] Step (4): The powder obtained in step (3) is mixed with an auxiliary agent and placed in an atmosphere furnace for high-temperature activation carbonization, wherein the mass ratio of the auxiliary agent is 2-10%, and an inert atmosphere of any one of nitrogen, argon, ammonia, and hydrogen-argon mixed gas is introduced. The carbonization temperature in the first stage is 700-900°C, preferably 800-850°C, the heating rate is 5-10°C / min, and the carbonization time is 1-2h. The carbonization temperature in the second stage is 1000-1300°C, preferably 1100-1200°C, the heating rate is 3-6°C / min, and the carbonization time is 2-3h. After the atmosphere furnace is cooled to room temperature, the obtained powder is washed with water or pickled at room temperature. The acid solution used for pickling is at least one of hydrochloric acid, sulfuric acid, and nitric acid, and the concentration is 0.5-2M. After drying, screening is performed to obtain a biomass-based hard carbon negative electrode active material with a median particle size of 5-10μm.

[0082] Preferably, in the present invention, the liquid phase modification in step 1 is carried out in an alcohol-water solution under closed conditions, the liquid phase modification temperature is 80-90° C., and the liquid phase modification time is 1-6 hours, wherein the alcohol-water solution is a mixed solution of ethanol and water, and the volume ratio of ethanol to water is 1:(1-4).

[0083] Example 1

[0084] Step (1): placing lignocellulosic biomass (coconut shell) in an aqueous solution (modified liquid) containing a functional additive (ammonium oxalate) at 80-90° C. for liquid phase modification for 6 h, wherein the amount of the functional additive added is 3% of the mass of the biomass, followed by drying, crushing, and sieving to obtain a powder (modified material A) with a median particle size of about 50 μm;

[0085] Step (2): prepare a sodium hydroxide solution with a concentration of 2M and a hydrochloric acid solution with a concentration of 6M, first place the biomass powder in the sodium hydroxide solution, control the liquid-to-solid ratio (ml / g) to 6:1, react at 60°C and 0.3MPa for 5h, filter press after the reaction, wash the filter residue with water and dry it, then place it in a hydrochloric acid solution, control the liquid-to-solid ratio (ml / g) to 4:1, react at 30°C with ultrasound assistance for 6h, filter press after the reaction, wash the filter residue with water and dry it to obtain the modified biomass powder (modified material B);

[0086] Step (3): the modified biomass powder obtained in step (2) is placed in an atmosphere furnace and subjected to gas phase modification treatment in a mixed atmosphere of nitrogen and oxygen (oxygen content is 15v%), the temperature is raised to 300°C (marked as T1) at a rate of 5°C / min and kept for 2h, and then cooled to room temperature and ground to obtain modified material C;

[0087] Step (4): The modified material C obtained in step (3) is mixed evenly with the functional additive (iron trifluoromethanesulfonate) and loaded into an atmosphere furnace for gradient heat treatment in Ar. The amount of the functional additive added is 6% of the mass of the modified material C. The gradient heat treatment process is first increased to 800°C (marked as T2) at a rate of 10°C / min and kept warm for 1 hour, then increased to 1200°C (marked as T3) at a rate of 5°C / min and kept warm for 2 hours. After cooling to room temperature, it is washed and dried, and then ground, crushed and sieved to obtain a cellulose-based hard carbon negative electrode active material (active material).

[0088] The active material, conductive carbon black and sodium alginate (SA) with a mass ratio of 90:5:5 were slurried and coated on the current collector (Cu foil) to form a carbon negative electrode. The carbon electrode was used as the working electrode, the sodium sheet was used as the counter electrode, 1 mol / L NaPF6 DME was used as the electrolyte, and the glass fiber was used as the diaphragm. The CR2032 button cell was assembled in a dry glove box filled with argon. The electrochemical performance was tested at room temperature (25°C) in the voltage range of 0.01-2.0V. The current density of the constant current charge and discharge test was 0.1C (1C=300mA / g), 0.2C, 0.4C, 1C, 2C, 4C, 10C, and 20C. At room temperature, the first reversible capacity of 0.1C was 341mAh / g, the first coulombic efficiency was 83.6%, and the capacity retention rate was 94.2% after 200 cycles. Under rapid charge and discharge conditions at 20C, its reversible specific capacity is 122mAh / g.

[0089] Example 2

[0090] Compared with Example 1, the only difference is that the conditions of step 1 are changed, and the experimental groups are:

[0091] Group A: The solvent of the modified solution was changed to 10v% ethanol aqueous solution;

[0092] Group B: the functional additive was changed to ammonium fluoride;

[0093] Group C: nitrogen was introduced into the system during the liquid phase modification stage, and the pressure during the treatment stage was maintained at 0.2-0.3 MPa;

[0094] Other operations and parameters are the same as those in Example 1, and the test is carried out according to the method of Example 1, and the results are respectively:

[0095] Group A: The first reversible capacity at 0.1C at room temperature is 358mAh / g, the first Coulombic efficiency is 83.1%, and the capacity retention rate after 200 cycles is 95.1%. Under fast charge and discharge conditions at 20C, the reversible specific capacity is 135mAh / g.

[0096] Group B: The first reversible capacity at 0.1C at room temperature is 349mAh / g, the first coulombic efficiency is 84.5%, and the capacity retention rate after 200 cycles is 94.8%. Under fast charge and discharge conditions at 20C, its reversible specific capacity is 125mAh / g.

[0097] Group C: The first reversible capacity at 0.1C at room temperature is 360mAh / g, the first Coulombic efficiency is 84.9%, and the capacity retention rate after 200 cycles is 95.4%. Under fast charge and discharge conditions at 20C, its reversible specific capacity is 137mAh / g.

[0098] Compared with Example 1, it can be seen that liquid phase modification in the preferred alcohol-water system can further enhance the modification effect. In addition, it can be seen from Group B and Group C that a better synergistic modification effect can be obtained under the F-containing auxiliary agent or pressurized liquid phase modification.

[0099] Example 3

[0100] Compared with Example 1, the only difference is that the conditions of step 3 are changed, and the experimental groups are:

[0101] Group A: In step 3, the biomass powder modified in step 2 is pre-mixed with 15% by weight of ammonium persulfate, and then subjected to the gas phase modification treatment;

[0102] Group B: Based on Group A, the gas phase modification treatment is carried out in a rotary kiln;

[0103] Other operations and parameters are the same as those in Example 1, and the test is carried out according to the method of Example 1, and the results are respectively:

[0104] Group A: At room temperature, the first reversible capacity at 0.1C is 367mAh / g, the first coulombic efficiency is 83.1%, and the capacity retention rate after 200 cycles is 95.5%. Under fast charge and discharge conditions at 20C, the reversible specific capacity is 139mAh / g.

[0105] Group B: At room temperature, the first reversible capacity at 0.1C is 381mAh / g, the first Coulombic efficiency is 82.4%, and the capacity retention rate after 200 cycles is 96.4%. Under fast charge and discharge conditions at 20C, the reversible specific capacity is 146mAh / g.

[0106] It can be seen from Examples 1 and 3 that, based on the gas phase modification, further introducing certain auxiliary agents can further enhance the modification effect. Moreover, further coordinating with the dynamic gas phase modification of the rotary kiln can further enhance the modification effect.

[0107] Example 4

[0108] Compared with Example 1, the only difference is that the conditions of step 4 are changed. The difference is:

[0109] Group A: The additive was changed to sodium hexafluoroferrate and nickel trifluoromethanesulfonate in a weight ratio of 1:1;

[0110] Group B: The additives were changed to sodium hexafluoroferrate, nickel trifluoromethanesulfonate and sodium carbonate in a weight ratio of 4.5:4.5:1;

[0111] The total additive and other operations and parameters are the same as those in Example 1, and the test is carried out according to the method of Example 1. The results are:

[0112] Group A: At room temperature, the first reversible capacity at 0.1C is 362mAh / g, the first coulombic efficiency is 85.4%, and the capacity retention rate after 200 cycles is 95.3%. Under fast charge and discharge conditions at 20C, the reversible specific capacity is 129mAh / g.

[0113] Group B: At room temperature, the first reversible capacity at 0.1C is 376mAh / g, the first coulombic efficiency is 89.1%, and the capacity retention rate after 200 cycles is 97.6%. Under fast charge and discharge conditions at 20C, the reversible specific capacity is 137mAh / g.

[0114] It can be seen from Examples 1 and 4 that the use of the combined auxiliary agents, especially further auxiliary auxiliary agents, can further enhance the technical effect.

[0115] Example 5

[0116] Compared with Example 1, the only difference is that other operating parameters such as the type of biomass are changed. The experimental groups are:

[0117] Group A: In step 1, the biomass is bagasse; the functional additive is 5% of the weight of the biomass; in step 2, the concentration of the alkali solution is 1.5M, the temperature of the alkali treatment stage is 50°C, and the treatment time is 6h; the concentration of the acid solution is 5M, and the acid solution treatment time is 4h; in step 3, the mixed atmosphere is air, the temperature T1 is 350°C, and the insulation time at this temperature is 1h; in step 4, the functional additive is 4% of the weight of the modified material C; the temperature T2 is 700°C, and the insulation time at this temperature is 2h; the temperature T3 is 1300°C, and the insulation time at this temperature is 1h;

[0118] Group B: In step 1, the biomass is walnut shells, and the functional additive is 1% of the weight of the biomass; in step 2, the concentration of the alkali solution is 2.5M, the temperature of the alkali treatment stage is 40°C, and the treatment time is 10h; the concentration of the acid solution is 2M, and the acid treatment time is 10h; in step 3, the temperature T1 is 250°C, and the insulation time at this temperature is 3h; in step 4, the functional additive is 8% of the weight of the modified material C; the temperature T2 is 900°C, and the insulation time at this temperature is 1h; the temperature T3 is 1100°C, and the insulation time at this temperature is 3h;

[0119] The test was carried out according to the method of Example 1, and the results were:

[0120] Group A: The first reversible capacity at 0.1C at room temperature is 325mAh / g, the first coulombic efficiency is 74.3%, and the capacity retention rate after 200 cycles is 91.8%. Under fast charge and discharge conditions at 20C, its reversible specific capacity is 110mAh / g.

[0121] Group B: The first reversible capacity at 0.1C at room temperature is 320mAh / g, the first coulombic efficiency is 81.4%, and the capacity retention rate after 200 cycles is 93.9%. Under fast charge and discharge conditions at 20C, its reversible specific capacity is 92mAh / g.

[0122] Comparative Example 1

[0123] Compared with Example 1, the only difference is that the liquid phase modification treatment in step 1 is not performed, but the biomass is directly crushed and screened before the subsequent steps. Other operations and parameters are the same as in Example 1.

[0124] Tested according to the method of Example 1, the results are:

[0125] At room temperature, the first reversible capacity at 0.1C is 294mAh / g, the first coulombic efficiency is 79.3%, and the capacity retention rate after 200 cycles is 87.4%. Under fast charge and discharge conditions at 20C, its reversible specific capacity is 73mAh / g.

[0126] Comparative Example 2

[0127] Compared with Example 1, the only difference is that no homogenizer is added in the liquid phase modification process in step 1, and other operations and parameters are the same as in Example 1.

[0128] Tested according to the method of Example 1, the results are:

[0129] At room temperature, the first reversible capacity at 0.1C is 303mAh / g, the first coulombic efficiency is 83.8%, and the capacity retention rate after 200 cycles is 86.2%. Under fast charge and discharge conditions at 20C, its reversible specific capacity is 75mAh / g.

[0130] Comparative Example 3

[0131] Compared with Example 1, the only difference is that the order of step 2 and step 3 is exchanged. For example, the biomass powder obtained in step 1 is directly processed in step 3, and then processed in steps 2 and 4. Other operations and parameters are the same as in Example 1.

[0132] Tested according to the method of Example 1, the results are:

[0133] At room temperature, the first reversible capacity at 0.1C is 301mAh / g, the first coulombic efficiency is 77.9%, and the capacity retention rate after 200 cycles is 89.2%. Under fast charge and discharge conditions at 20C, its reversible specific capacity is 78mAh / g.

[0134] Comparative Example 4

[0135] Compared with Example 1, the only difference is that in step 3, the atmosphere of the gas phase treatment is changed to nitrogen, and the other operations and parameters are the same as in Example 1.

[0136] Tested according to the method of Example 1, the results are:

[0137] At room temperature, the first reversible capacity at 0.1C is 287mAhh / g, the first coulombic efficiency is 79.2%, and the capacity retention rate after 200 cycles is 87.1%. Under fast charge and discharge conditions at 20C, its reversible specific capacity is 69mAh / g.

[0138] Comparative Example 5

[0139] Compared with Example 1, the only difference is that in step 3, the modified biomass powder and 15% hydrogen peroxide solution are loaded into the reactor for liquid phase modification, the reaction time is 12 hours, the reaction temperature is 180°C, the reaction is completed and the filter is filtered, the filter residue is washed with water and dried, and then ground to obtain modified biomass C. Other operations and parameters are the same as in Example 1.

[0140] Tested according to the method of Example 1, the results are:

[0141] At room temperature, the first reversible capacity at 0.1C is 296Ah / g, the first Coulombic efficiency is 81.3%, and the capacity retention rate after 200 cycles is 86.4%. Under fast charge and discharge conditions at 20C, its reversible specific capacity is 77mAh / g.

[0142] Comparative Example 6

[0143] Compared with Example 1, the only difference is that in step 4, the functional additive is eliminated, and the other operations and parameters are the same as Example 1.

[0144] Tested according to the method of Example 1, the results are:

[0145] At room temperature, the first reversible capacity at 0.1C is 292mAh / g, the first coulombic efficiency is 84.1%, and the capacity retention rate after 200 cycles is 88.2%. Under fast charge and discharge conditions at 20C, its reversible specific capacity is 73mAh / g.

Claims

1. A method for preparing a lignocellulose-based hard carbon active material, characterized in that the steps include: Step (1): The lignocellulosic biomass is placed in a solution A containing a homogenizer and subjected to liquid phase modification at a temperature T1, followed by solid-liquid separation, and the modified biomass A is collected; Then, the modified biomass A is sequentially treated with alkali solution modification and acid solution modification to obtain modified biomass B; The homogenizer is capable of ionizing NH4 + Ionic compound; the temperature T1 is 40 to 120°C; Step (2): The modified biomass B is subjected to gas phase modification treatment in an oxygen-containing atmosphere at a temperature T2 to obtain a modified biomass C; the temperature T2 is 200 to 400° C.; Step (3): The modified biomass C and the additive are mixed, and the mixture is pre-heated at a temperature T3 for a first stage, and then heat-insulated at a temperature T4 for a second stage to obtain the lignocellulose-based hard carbon active material; The auxiliary agent includes a transition metal source; the temperature T3 is 700-900°C; and the temperature T4 is 1000-1300°C.

2. The method for preparing a lignocellulose-based hard carbon active material according to claim 1, characterized in that: The lignocellulosic biomass contains lignocellulose, preferably at least one of agricultural waste, agricultural derivatives and wood; Preferably, the agricultural waste includes at least one of rice straw, wheat straw, corn straw, bean straw, peanut straw, rape straw, sugarcane straw, cotton stalk, straw, bagasse, coconut shell, walnut shell, hazelnut shell, almond shell, macadamia shell, banana peel, grapefruit peel, and orange peel; Preferably, the agricultural derivatives include at least one of corn cobs, lotus pods, oak seeds, pine cones, bamboo stalks, and reeds; Preferably, the wood includes at least one of pine, camphor, poplar, oak and fir.

3. The method for preparing a lignocellulose-based hard carbon active material according to claim 1, characterized in that: The homogenizer includes one or more of ammonium oxalate, ammonium chloride, ammonium bifluoride, ammonium formate, ammonium citrate, ammonium fluoroborate, and ammonium fluoride; preferably at least one of ammonium fluoride, ammonium bifluoride, and ammonium fluoroborate; Preferably, the homogenizer is 0.05-5% by weight of the lignocellulosic biomass.

4. The method for preparing a lignocellulose-based hard carbon active material according to claim 1 or 3, characterized in that: The liquid phase modification treatment stage is pressurized by atmosphere A; the atmosphere A is at least one of nitrogen, argon, carbon dioxide, and air; Preferably, the solvent in the liquid phase modification stage is an aqueous solvent; preferably water or a mixed solvent of water and an organic solvent; the organic solvent is a water-soluble organic solvent, more preferably a C1-C6 alcohol; Preferably, the pressurized pressure is 0.2-0.5 MPa; Preferably, the temperature of liquid phase modification is 80-90°C; Preferably, the liquid phase modification time is 4 to 8 hours; Preferably, the alkaline solute in the alkali solution includes at least one of a hydroxide and a carbonate of an alkali metal; Preferably, the concentration of the alkaline solute in the alkali solution is 0.5 to 3 M; Preferably, the alkali solution modification time is 4 to 12 hours; Preferably, the acidic solute in the acid solution includes at least one of hydrochloric acid, sulfuric acid, phosphoric acid, and nitric acid; Preferably, the concentration of the acidic solute in the acid solution is 2 to 6 M; Preferably, the acid modification time is 4 to 12 hours.

5. The method for preparing a lignocellulose-based hard carbon active material according to claim 1, characterized in that: The oxygen-containing atmosphere is at least one of oxygen, air, an oxygen-diluent mixture, and an air-diluent mixture; Preferably, the modified biomass B is pre-mixed with an additive and then subjected to gas phase modification treatment in the oxygen-containing atmosphere; wherein the additive comprises at least one of ammonium persulfate, sodium persulfate, potassium ferrate, and sodium ferrate; Preferably, the additive is 5 to 25% by weight of the modified biomass B; Preferably, the gas-solid modification process is carried out in a rotary kiln or a fluidized bed furnace; Preferably, the temperature of gas phase modification is 250-350°C; Preferably, the time of gas phase modification is 1 to 5 hours.

6. The method for preparing a lignocellulose-based hard carbon active material according to claim 1, characterized in that: In step (3), the auxiliary agent includes at least one of sodium hexafluoroferrate, potassium hexafluoroferrate, ferric trifluoromethanesulfonate, potassium ferrocyanide, sodium ferrocyanide, nickel trifluoromethanesulfonate, nickel tetrafluoroborate, cobalt trifluoromethanesulfonate, and potassium cobalt cyanide; Preferably, the auxiliary agent further comprises an auxiliary agent, wherein the auxiliary agent comprises at least one of sodium trifluoromethanesulfonate, sodium carbonate, sodium hydroxide and sodium carboxylate; Preferably, the content of the auxiliary agent in the auxiliary agent is less than 50wt%; Preferably, the auxiliary agent is 0.5-10% of the weight of the modified biomass C.

7. The method for preparing a lignocellulose-based hard carbon active material according to claim 1 or 6, characterized in that: The first stage of heat preservation has a heat preservation time of 1 to 2 hours; Preferably, the second insulation period is 1 to 3 hours.

8. A lignocellulose-based hard carbon active material obtained by the preparation method according to any one of claims 1 to 7.

9. An application of a lignocellulose-based hard carbon active material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: It is used as negative electrode active material to prepare sodium ion batteries.

10. A sodium ion battery, characterized in that: It comprises a lignocellulose-based hard carbon active material obtained by the preparation method according to any one of claims 1 to 7; Preferably, the negative electrode of the sodium ion battery contains the lignocellulose-based hard carbon active material.

Citation Information

Patent Citations

  • Bamboo charcoal-based active material, bamboo charcoal-based silicon-carbon composite active material and preparation and application of bamboo charcoal-based silicon-carbon composite active material

    CN117023577A

  • Biomass-based hard carbon active material, preparation thereof and application of biomass-based hard carbon active material in sodium-ion battery

    CN118343733A

  • Bamboo-based hard carbon active material, preparation thereof and application of bamboo-based hard carbon active material in sodium-ion battery

    CN118343734A

  • Hard carbon negative electrode material and preparation method therefor, and secondary battery

    WO2024138837A1

Cited By

  • Preparation method of hard carbon derived from bagasse and application of hard carbon in sodium battery

    CN119976798A

  • A method for preparing hard carbon derived from sugarcane bagasse and its application in sodium batteries

    CN119976798B